Efficacy of intermittent versus daily vitamin D supplementation on improving circulating 25(OH)D concentration: a Bayesian network meta-analysis of randomized controlled trials - Zhuang, Yan; Zhu, Zhe; Chi, Peihan; Zhou, Haibo; Peng, Zhicheng; Cheng, Haoyue; Xin, Xing; Luo, Wenliang; Si, Shuting; Mo, Minjia; Chen, Danqing; Liu, Hui; et al. (Frontiers in Nutrition, 2023)
Background Vitamin D deficiency is a widespread issue globally, resulting in increased use of vitamin D supplements. However, it is unclear whether intermittent (weekly or monthly) vitamin D supplementation is as effective as daily supplementation in improving circulating 25-hydroxyvitamin D [25(OH)D] levels. Methods Three databases including Medline, EMBASE, and the Cochrane Library were systematically searched up to 10 November 2020. The risk of bias was evaluated according to Cochrane Collaboration’s tool for rating methodological quality assessment. Direct and indirect comparisons between interventions and controls were performed by a Bayesian network meta-analysis (NMA), where the mean difference (MD) and its 95% confidence interval (CI) were used to indicate the efficacy. Results This NMA analysis included 116 RCTs with a total of 11,376 participants. Generally, we observed that 25(OH)D concentrations were significantly elevated regardless of vitamin D supplementation frequency. Although the findings of SUCRA indicated that daily vitamin D supplementation had a higher rank value than intermittent supplementation when the supplement dosage was similar, no statistically significant pooled mean differences of 25(OH)D concentration were noted between the daily supplementation group and intermittent supplementation group. Additionally, weekly supplementation with a total of 600,000 IU vitamin D supplementation during 3 months had the best efficacy in elevating 25(OH)D concentration (pooled MD = 63 nmol/L, 95%CI: 49–77). To achieve optimal 25(OH)D concentration (>75 nmol/L), we recommend 60,000 IU vitamin D supplementation monthly (~2,000 IU/day). Conclusion The efficacy of intermittent vitamin D supplementation was similar to daily supplementation. Coupled with its convenience, the frequency and dosage of intermittent vitamin D supplements were recommended to reach the optimal 25(OH)D level. Systematic review registration:https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=257257, PROSPERO CRD42021257257.